The cardiac surgery patient and the use of transitional care: Impact on post-operative complications and hospital readmissions. A structured narrative review. - Carucci, Alessia; D'Agostino, Fabio; Cesare, Manuele (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Cardiac surgery patients are clinically and emotionally complex. Surgery represents a highly critical event not only for patients but also for their families. Care for these patients should not end at discharge; rather, ongoing support and education are essential. This underlines the relevance of Transitional Care (TC), characterized by nurse-led follow-up programs to ensure continuity of care and effective disease management post-discharge. However, the impact of such interventions remains poorly documented. This structured narrative review aims to assess the effectiveness of nurse-led follow-up models in managing post-operative complications and hospital readmissions in patients after cardiac surgery.Study design: A structured narrative review was conducted to explore existing TC models and their effects on post-operative complications and hospital readmissions in patients discharged after cardiac surgery.Methods: A comprehensive search strategy was implemented using PubMed and Cochrane Library databases, covering literature published from December 2014 to February 2025. The review was guided by the PIO framework: Population (adults undergoing cardiac surgery), Intervention (nurse-led Transitional Care programs post-discharge), and Outcome (reduction in post-operative complications and hospital readmissions). Studies were included if they were quantitative, experimental or observational designs, involved adult patients, evaluated nursing-led transitional care interventions and published in English. Studies involving pediatric populations, non-nursing interventions, or qualitative methods were excluded.Results: After applying inclusion and exclusion criteria, seven studies were selected. Two main TC strategies were identified: post-discharge home visits and tele-nursing. These models were associated with improved medication adherence and reduced post-operative complications, including anxiety, depression, bleeding, thromboembolism, and lower hospital readmission rates.Conclusions: Nurse-led TC interventions after cardiac surgery demonstrate promising potential to enhance recovery, ensure greater continuity of care, and reduce adverse events and healthcare system burden. Implementing structured follow-up TC programs can support sustained patient engagement, promote treatment adherence, and contribute to improved long-term outcomes.